Pengaruh Family Ownership, CEO duality, dan Political Connection terhadap Firm Performance - Dinara Dosen; Rousilita Suhendah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the effect of family ownership and CEO duality moderated by political connection on firm performance. Using purposive sampling method, the research observation uses data from 34 companies in the mining industry in the mining sector listed on the Indonesia Stock Exchange (IDX) during 2018-2023 totaling 200 data samples. The data was tested using software Eviews 12 with moderation regression models with the most suitable model estimation is Common Effect Model (CEM). To measure the dependent variable from this study, which is firm performance, this study uses Return on Assets (ROA) as a parameter. As a result of the moderation regression, family ownership has a positive significant effect on firm performance. CEO Duality has no effect on firm performance. Family ownership moderated by political connection has no effect on firm performance. Lastly, CEO Duality moderated by political connection has no effect on firm performance.